A policy landscape analysis of the school-based vaccination program in the Philippines a case study in Region IV-A - Palola, Tricia Kaye F.
School-based immunization (SBI) has emerged as a strategic approach to increase vaccine coverage among school-aged children. SBI was introduced in the Philippines in 2013 to complement routine immunization and capture missed childhood vaccinations. However, coverage has continued to decline since 2015, further compounded by the 2019 polio outbreak, the Dengvaxia controversy, and prolonged COVID-19 school closures. Implementing SBI is inherently complex. Although national guidelines from the Department of Education (DepEd) and the Department of Health (DOH) aim to streamline processes, actual implementation unfolds across multiple levels - from national policy formulation to district and school-level execution.